The Trauma of Autonomy: : Neoliberalism and the Forms of the Subject’s Exile - Asimiadis, Dionysis; Kagioglou, Foteini (Dia-noesis: A Journal of Philosophy, 2025)
The paper investigates the manner neoliberalism, as a regime of subjectivation, turns autonomy as a space of freedom into trauma. By the instrumentality of the values of personal responsibility, continuous self-enhancement, and commodifying the self, subjects are compelled into a situation of solitary existence: they are estranged from common meanings, social relationships, and other forms of belonging. Work, consumption, and the performativism of identity are disciplining agencies that conceal rather than erase the trauma originating in the estrangement from the social nucleus. The paper attempts to map these modalities of solitude in the subject under psychoanalytic, biopolitical, and cultural axes; it examines the notion of the trauma of autonomy as a structuring component of the neoliberal experience . Last, it suggests that a comprehensive understanding of neoliberal trauma can provide new avenues for a rewriting of collectivity, remembrance, and resilience against the background of diffuse exile.